Class Teacher Strategies in Shaping Students Characters in Elementary Schools (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
The purpose of this study is to identify the strategy used by educators in grade IV SD Negeri 03 Pondok Ranji to build student character, factors that support and hinder the implementation of learning approaches used by educators to build student character and efforts made by educators to overcome challenges that hinder the implementation of this approach. This research uses qualitative approach and descriptive method because it utilizes words from field informants directly. Data collection methods through observation and interviews, as well as documentation They conduct interviews with principals, homeroom teachers, teachers, students, and parents. with a paper tool with a list of questions and a phone to record. The results showed that first, the classroom teacher's strategy to build student character consists of examples or models of positive behavior, habituation, second integration in teaching activities, mentoring and supervision, and third creating a conducive learning environment, involving active student participation, assigning assignments, and improving students' social and emotional skills. and last fouth, a number of efforts are made to overcome challenges, such as incorporating character education into learning and establishing relationships with parents of students.